Does information disclosure among public hospitals stimulate medical cost change efforts? A pilot study in Shanghai - Ya-jing Chen; Rui-Xin Wang; Jin-yan Tang; Xiao-hua Ying (BMC, 2023)
Abstract Background In 2013, the Shanghai Hospital Development Center issued a policy to advocate public hospitals to report their information about costs on diseases. The objective was to evaluate the impact of interhospital disclosure of costs on diseases on medical costs and compare costs per case following information disclosure between hospitals of different rankings. Methods The study uses the hospital-level performance report issued by Shanghai Hospital Development Center in the fourth quarter of 2013, which covers quarterly aggregated hospital-level discharge data from 14 tertiary public hospitals participating in thyroid malignant tumors and colorectal malignant tumors information disclosure from the first quarter of 2012 to the third quarter of 2020. An interrupted time series model with segmented regression analysis is employed to examine changes in quarterly trends with respect to costs per case and length of stay before and after information disclosure. We identified high- and low-cost hospitals by ranking them on a costs per case basis per disease group. Results This research identified significant differences in cost changes for thyroid malignant tumors and colorectal malignant tumors between hospitals after disclosing information. A hospital's discharge costs per case for thyroid malignant tumors increased significantly among top-cost hospitals (1629.251 RMB, P = 0.019), while decreased for thyroid and colorectal malignant tumors among low-cost hospitals (-1504.189 RMB, P = 0.003; -6511.650 RMB, P = 0.024, respectively). Conclusion Our findings indicate that information disclosure of costs on diseases results in changes in discharge costs per case. And low-cost hospitals continued to maintain their leading edge, whereas the high-cost hospitals changed their position in the industry by reducing discharge costs per case after information disclosure.